Design, development and validation of a model of problem solving for Egyptian Science classes - Shahat, M.; Ohle, A.; Treagust, David; Fischer, H. (Springer Netherlands, 2013)
Educators and policymakers envision the future of education in Egypt as enabling learners to acquire scientific inquiry and problem-solving skills. In this article, we describe the validation of a model for problem solving and the design of instruments for evaluating new teaching methods in Egyptian science classes. The instruments were based on an established model for problem solving and were designed to assess seventh grade students’ problem solving, experimental strategy knowledge, achievement and motivation towards science. The test for assessing students’ knowledge has been developed based on the topic, density and buoyancy which will be taught in seventh grade in a later intervention study. The instruments were partly self-developed and partly adapted from newly performed studies on strategy knowledge and problem solving in Germany. All instruments were translated into Arabic; the translation process and quality control are described. In order to determine the quality of the instruments, 44 students in Egypt completed the questionnaires and tests. The study’s aim to develop and validate the instruments did require an ad hoc and typical sample which was drawn from an accessible population. Accordingly, the characteristics of the sample are described. Data were analysed according to the classical test theory, but to underpin the results, the instruments were additionally analysed using the even stronger Rasch model. The findings demonstrated the reliability of the items and aspects of validity. In addition, this study showed how test items can be successfully developed and adapted in an international study and applied in a different language.